Evolution of Earth’s magnetosheath as a planar magnetic structure - Shaikh, Zubair I.; Raghav, Anil N. (My University, 2022)
In general, the Earth’s magnetosheath (MS) plasma is highly compressed, heated, and turbulent. Thus, it provides preferential conditions in which to investigate plasma turbulence, dissipation, and transport, which are the major unresolved issues in the modern space era. Here, we examine plasma evolution features using 10 crossovers of the Wind spacecraft through the dawn and dusk sides of the Earth’s magnetosheath. The study demonstrates explicitly that the magnetosheath is transformed into planar magnetic structure (PMS). We found that, on average, 77 . 56 per cent of the whole magnetosheath transit-time region is transformed into PMS. The average thickness of the magnetosheath-moulded PMS is ∼5.74 h. We also noticed that a few plasma parameters, such as B mag and β, N p and T p , N p and V p , and T p and V p , show high correlation coefficients. Also, the regression analysis of these variables suggests that they are dependent on each other equally. We propose that the MS evolves into PMS due to the draping of plasma at the magnetopause surface, or the alignment of a discontinuity present in the MS due to high compression caused by the solar wind. However , convection of solar-wind-originated PMS into the MS should not be overlooked.
Keywords: Magnetic fields; Turbulence; Solar wind; Planets and satellites: magnetic fields